Realizing Minimum Service Standards for Food Based on Local Wisdom in Central Halmahera Regency - Abdurachman F., Maman (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Realizing minimum service standards in the food sector is the responsibility of the Government in general, and the Government of Central Halmahera Regency in particular. Various efforts have been made, among others, through the approach of implementing "local wisdom" on food. The local wisdom in question is a culture passed down from generation to generation by the community that sago (Metroxylon sago Rottb) is the staple food after kasbi (cassava / Manihot esculenta Crantz), betatas (sweet potato / Ipomoea batatas L), banana (Musa paradisiaca L) , and maize (Zea mays L). However, in the end all of them have become alternative foods, replaced by rice (Oriza sativa L.). There are socio-cultural values   contained therein that want to be preserved through this study. This study is a descriptive subjective which tries to integrate between intuitive experience and an understanding of the opportunities that exist The essence of local wisdom to food based on several previous studies and studies shows that there are other values   that accompany it, namely the realization of food security in the area concerned, this is shown by the results of research by Tuti Gantini (2016). which states that “vulnerability to food insecurity with local wisdom is smaller than on vulnerability to food insecurity without local wisdom ”. According to Tupan (2014), "One of the efforts to increase the acceleration of the movement to diversify food consumption in order to achieve food security is to restore the diversification pattern of food consumption that has taken root in society as local wisdom" According to Soerjani (2005) in Marcus J. Pattinama (2009). ), by exploring and developing local wisdom, it can not only be relieving, but can also be avoided (preventing) due to the large amount of resources for the next generation. The results of the study here ultimately point to the efforts that need to be done, namely: (1). Preserving Local Wisdom and Culture on Food, (2). Collaborating skills with local wisdom on food, (3). Focus on cultivating selected superior commodities, (4). Capacity and capability enhancement, and (5). Synergy, integrity, communication and collaboration between related agencies. From the results of this study, it is hoped that the Regional Government as a stakeholder should be consistent and committed to implementing these efforts